2018
DOI: 10.1101/338178
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell transcriptomics identifies CD44 as a new marker and regulator of haematopoietic stem cells development

Abstract: The endothelial to haematopoietic transition (EHT) is the process whereby haemogenic endothelium differentiates into haematopoietic stem and progenitor cells (HSPCs). The intermediary steps of this process are unclear, in particular the identity of endothelial cells that give rise to HSPCs is unknown. Using single-cell transcriptome analysis and antibody screening we identified CD44 as a new marker of EHT enabling us to isolate robustly the different stages of EHT in the aorta gonad mesonephros (AGM) region. T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…To compare the molecular features of HE cells in placenta and AGM, we first verified that CD44 can also be used to enrich HE cells in the AGM region (Figures S3A and B), consistent with a recent report (Oatley et al, 2020). Then we enriched HE cells and non-HE cells (CD44 -ECs) from AGM and placenta at E11.0 and performed modified Smart-seq2 due to the rarity of HE cells (Figure S3C, Table S2).…”
Section: Comparison Of Placental and Agm He Cellssupporting
confidence: 81%
See 1 more Smart Citation
“…To compare the molecular features of HE cells in placenta and AGM, we first verified that CD44 can also be used to enrich HE cells in the AGM region (Figures S3A and B), consistent with a recent report (Oatley et al, 2020). Then we enriched HE cells and non-HE cells (CD44 -ECs) from AGM and placenta at E11.0 and performed modified Smart-seq2 due to the rarity of HE cells (Figure S3C, Table S2).…”
Section: Comparison Of Placental and Agm He Cellssupporting
confidence: 81%
“…During mouse embryogenesis, HE cells can be identified in different anatomical locations including yolk sac and AGM (Gao et al, 2018). In this study, for the first time, we identified HE cells in the mouse placenta by using a surface marker CD44 that can purify ECs with hemogenic potential as reported in mouse and human AGM region recently (Oatley et al, 2020, Zeng et al, 2019. In addition, we also verified the conserved expression of CD44 in human placental ECs.…”
Section: Discussionmentioning
confidence: 66%
“…Noteworthy, RUNX3 expression was specifically associated with the monocyte 323 subcluster ( Figure 6I progenitors, we observed high levels of CD44 mRNA expression, a protein reported to be 347 expressed in normal and leukemic hematopoietic cells (Zöller, 2015). Recently, a single 348 cell transcriptome analysis reported that CD44 marks hematopoietic stem and progenitor 349 cells in the mouse AGM, and functions in endothelium to hematopoietic transition, EHT 350 (Oatley et al, 2018). We confirmed CD44 expression on the aortic endothelium of the 351 AGM region and, showed expression on some of the vessels in the yolk sac together with 352 the hematopoietic clusters associated with these.…”
Section: Identification Of Membrane Markers Of Lineage Primed Progenimentioning
confidence: 74%
“…Other studies have focused on one or two developmental time points and compared the different cell populations from non-HEC to HSPCs with the aim of identifying, and ordering along a differentiation trajectory, the intermediate cellular states with the accompanying transcriptional stages. The identification of additional cell surface markers [69,71] and the use of further fluorescent reporter mouse lines [66,68,70] have made these isolation strategies ever more sophisticated.…”
Section: Molecular Details Of Ehtmentioning
confidence: 99%
“…The advent of single-cell RNA-Seq has allowed a more detailed dissection of the differentiation pathway from endothelial cell to haematopoietic cell [66,69,71]. Additional intermediate cellular states have been uncovered that can be ordered along a differentiation trajectory using pseudotime algorithms, which is most prominently marked by a gradual down-regulation of endothelial-specific genes and an up-regulation of haematopoietic genes.…”
Section: Molecular Details Of Ehtmentioning
confidence: 99%